Situation report of the CARE for the Czech and Slovak Republics - Mařiková-Kubková, Jana; Baxa, Peter (Hortus Artium Medievalium, 2012)
Abstract The centre of Europe, the territory of the today’s Czech and Slovak Republics, was Christianized sometime at the end of the 8thor at the beginning of the 9thcent. From this time stem solitary finds of churches. The main assemblage of architecture dates to the time span between 1sthalf of the 9thand the middle of the 11thcent. We know of about 30 such buildings, mostly of banal building types and scales. The only exceptions are three basilicas, one building with three apses, and one with transept. A scientific interest in early medieval architecture is to be traced back to the end of the 19thcent. in Bohemia, from the beginning of the 20thin Moravia, and since the 1920s/1930s in Slovakia. The excavation methods have undergone changes from a heritage conservation survey, through the methods of Prehistoric excavation to the current approach that makes use of modern geodetic and geophysical methods, building technology, and natural sciences.